Perspectives on the use of growth rate patterns in fossil ectotherm bones to characterise ancient continental environments: Case study in Late Neogene sites from northern Chad (Djurab). (November 2018) - Lapalus, Florian; Otero, Olga; Nekoulnang Djetounako, Clarisse; Adoum, Mahamat; Pinton, Aurélie; de Rafélis, Marc; Segalen, Loïc; Likius, Andossa; Vignaud, Patrick; Brunet, Michel; Garcia, Géraldine
Abstract: We investigate the feasibility and potential relevance of studying growth patterns in the bones of fossil freshwater ectotherms with the aim of developing new markers for continental palaeoenvironments and climates. This prospective study is based on Late Neogene material from Chad. It thus provides preliminary results that interest the reconstruction of paleoenvironments in ancient hominid bearing sites and that also document paleoenvironmental changes in continental Africa along a critical time period for global change. We prepared a set of various fish bones and turtle plates from Chadian Mio-Pliocene fossiliferous areas. We were able to analyse growth rates recorded during the course of the life of the animals in about half of the fossils initially sampled for the study. The main conclusions are: 1) the absence of a relationship between the external aspect of the fossils and the preservation of the growth marks, which means that visible features are not helpful in primary sampling; 2) at least in the Neogene Chadian sites, cathodoluminescence does not help to reveal growth marks; 3) growth rate patterns observed in the section of the body of the fin spines in claroteids, latids and polypterids and in pelomedusoid plates seem to be informative about environmental control of animal growth; and 4) depending on the taxa, different environmental informations can be obtained. Highlights: Diagenesis affects bones sometimes with high variability in a same outcrop. Growth rates in fossil fish and turtle bones document paleo-seasonality and -aquatic habitats. The intensity of seasonal amplitude seems to vary along the Late Neogene in Central Chad.